2002
DOI: 10.1128/cdli.9.1.149-155.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiological Effects of Fumonisin B1 in Experimental Subchronic Mycotoxicoses in Rats

Abstract: Fumonisin B1 (FB1), the principal secondary metabolite produced by the fungus Fusarium verticillioides (Gibberella fujikuroi mating population A), is a potent toxin that can be found in fungus-contaminated corn and corn-based food products. We have investigated the immunobiological effects of subchronic dietary exposure to FB1 in male Wistar rats. Animals were fed with diets containing 0 (control) or 100 ppm of FB1 for 12 weeks. The total FB1 intake on day 90 was 810 mg/kg of body weight. Food consumption, bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
3
26
0
3
Order By: Relevance
“…However, there were a significant supression of response to ConA in mice treated with PPF in relation to the normal control without treatment with PPF, suggesting that the FB 1 in our conditions of experiment does not affect the specific cellular immune response but can suppress in specific immune response. Our results are partially in accordance with the data of Theumer et al (2002), which they had observed no significant effect on mitogeninduced proliferation of spleen cells in mice treated with FB 1 and stimulated with phytohemaglutinin mitogen (PHA). The inflammatory reaction is a non-specific response and Gonzalez et al (2000) reported that the NO produced by spleen macrophages has crucial role in P. brasiliensis defense.…”
Section: Discussionsupporting
confidence: 92%
“…However, there were a significant supression of response to ConA in mice treated with PPF in relation to the normal control without treatment with PPF, suggesting that the FB 1 in our conditions of experiment does not affect the specific cellular immune response but can suppress in specific immune response. Our results are partially in accordance with the data of Theumer et al (2002), which they had observed no significant effect on mitogeninduced proliferation of spleen cells in mice treated with FB 1 and stimulated with phytohemaglutinin mitogen (PHA). The inflammatory reaction is a non-specific response and Gonzalez et al (2000) reported that the NO produced by spleen macrophages has crucial role in P. brasiliensis defense.…”
Section: Discussionsupporting
confidence: 92%
“…These antioxidative properties were further confirmed in cell viability assays with KB-3-1 cells (Fig. 2d) [47]. FB 1 treatment decreased the H 2 O 2 production in peritoneal macrophages of rats in vivo and in vitro suggesting immunsuppressive effects, which could be related to a lower antitumour activity [47].…”
Section: Antioxidant Activities Of Enn and Beamentioning
confidence: 69%
“…2d) [47]. FB 1 treatment decreased the H 2 O 2 production in peritoneal macrophages of rats in vivo and in vitro suggesting immunsuppressive effects, which could be related to a lower antitumour activity [47]. So far, this study gives evidence that ENN and BEA possess antioxidative properties which have to be further characterised in more detail.…”
Section: Antioxidant Activities Of Enn and Beamentioning
confidence: 79%
“…The effect of subchronic dietary exposure to FB 1 was investigated in male Wistar rats (Theumer et al, 2002). After feeding a diet containing 100 ppm of FB 1 for 12 weeks no significant effect on mitogen induced in vivo and in vitro proliferation of spleen mononuclear cells was found.…”
Section: Discussionmentioning
confidence: 99%